Life-Span Development - Santrock, John W. (Dubuque : W.C. Brown Co. Publisher, 1989)
Life-Span Development, third edition, is about life's rhythm and meaning, and about weaving together a portrait of who we were, are, and will be. This text is about you and it is about me. It is about the life of every human being. It tells the story of human development from conception to death-from the point in time when life as we know it begins until the point in time when it ends. The complex and exciting story of how we develop, of how we become who we are, is written and presented in a manner that I believe you will find both informative and enjoyable.
The Life-Span Developmental Perspective -- Beginnings -- Infancy -- Early Childhood -- Middle and late Childhood -- Adolescence -- Early Adulthood -- Middle Adulthood -- Late Adulthood -- Death and Dying.
Includes bibliographical references and index.
Keywords: HUMAN DEVELOPMENT